Humanistic Philosophical Thinking in Religious Education: Conveying Humanity and Empathy in Religion to the Campus Community - Jamil, Hanifatun; Sayidah, Rahma Diana (Indonesian Journal of Research in Islamic Studies, 2025)
Background: Religious education aims to deepen understanding of religious doctrines while fostering character development through humanistic values and empathy. This study explores how integrating humanistic philosophy into religious education can promote freedom, responsibility, and social awareness, helping to prevent dogmatic interpretations of religion. Objective: This study aims to examine how a humanistic approach can enhance students' empathy and appreciation for religious diversity. Method: Using a library research method with content analysis, the study reviews relevant literature on humanistic philosophy in religious education. Result: Preliminary findings suggest that humanistic principles can be effectively incorporated into religious education, promoting inclusivity, empathy, and respect for others. Conclusion: The study concludes that a humanistic approach to religious education supports religious understanding and cultivates students' character, fostering respect for diversity and human dignity. Contribution: This research contributes to a more inclusive and socially relevant religious education that goes beyond doctrine to emphasise humanistic values in daily life.